Histamine H2 Receptor-Mediated Suppression of Intestinal Inflammation by Probiotic Lactobacillus reuteri - Chunxu Gao (American Society for Microbiology, 2015)
ABSTRACT Probiotics and commensal intestinal microbes suppress mammalian cytokine production and intestinal inflammation in various experimental model systems. Limited information exists regarding potential mechanisms of probiotic-mediated immunomodulation in vivo. In this report, we demonstrate that specific probiotic strains of Lactobacillus reuteri suppress intestinal inflammation in a trinitrobenzene sulfonic acid (TNBS)-induced mouse colitis model. Only strains that possess the hdc gene cluster, including the histidine decarboxylase and histidine-histamine antiporter genes, can suppress colitis and mucosal cytokine (interleukin-6 [IL-6] and IL-1β in the colon) gene expression. Suppression of acute colitis in mice was documented by diminished weight loss, colonic injury, serum amyloid A (SAA) protein concentrations, and reduced uptake of [18F]fluorodeoxyglucose ([18F]FDG) in the colon by positron emission tomography (PET). The ability of probiotic L. reuteri to suppress colitis depends on the presence of a bacterial histidine decarboxylase gene(s) in the intestinal microbiome, consumption of a histidine-containing diet, and signaling via the histamine H2 receptor (H2R). Collectively, luminal conversion of l-histidine to histamine by hdc+ L. reuteri activates H2R, and H2R signaling results in suppression of acute inflammation within the mouse colon.IMPORTANCE Probiotics are microorganisms that when administered in adequate amounts confer beneficial effects on the host. Supplementation with probiotic strains was shown to suppress intestinal inflammation in patients with inflammatory bowel disease and in rodent colitis models. However, the mechanisms of probiosis are not clear. Our current studies suggest that supplementation with hdc+ L. reuteri, which can convert l-histidine to histamine in the gut, resulted in suppression of colonic inflammation. These findings link luminal conversion of dietary components (amino acid metabolism) by gut microbes and probiotic-mediated suppression of colonic inflammation. The effective combination of diet, gut bacteria, and host receptor-mediated signaling may result in opportunities for therapeutic microbiology and provide clues for discovery and development of next-generation probiotics.